Investigating the effect of connectivity of top management team on their resilience - Fariborz Rahimnia; Shamsodin Nazemi; Yashar Moradian (Management Science Letters)
Nowadays, organizations are operating in a full of complex, ever changing and unpredictable environment, so that technological changes in providing goods and services, creating new organizational structures, new competitive methods and unique methods of sales indicate the importance of planning of top management team in line with the organizational success. Therefore, an attribute, which is important more than ever is resilience of top management team from two dimensions of its beliefs and adaptive capacity with these environmental events. Therefore, in this paper, the effect of connectivity of top management team on their resilience was investigated amongst 500 industrial active units located in northeast of Iran as the statistical population. Statistical sample was comprised of 139 organizations. Analysis results using structural equation modeling showed that the tested model had a goodness of fit to data. The effect of connectivity of top management team on efficacious beliefs of resilience and adaptive capacity of resilience was confirmed in line with related previous studies.